2016
DOI: 10.1002/pssa.201600619
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐processed high‐k oxide dielectric via deep ultraviolet and rapid thermal annealing for high‐performance MoS2 FETs

Abstract: So far most of MoS2‐based devices have been demonstrated on oxide gate dielectrics (e.g., SiO2, Al2O3, HfO2, etc) deposited by vacuum process or on polymer gate dielectrics. In this study, we report electrical characteristics of multilayer MoS2 transistors fabricated on solution‐processed high‐k AlOx gate dielectric via deep ultraviolet (DUV) activation in combination with rapid thermal annealing process at 250 °C. The solution‐processed AlOx sol–gel film exhibited low leakage current of about 1.49 μA cm−2 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…However, following this nucleation period, deposition of a nanometer‐thin conformal AlO x coating on the as‐deposited amorphous carbon layer was achieved. While charge carriers can directly tunnel through the nanometer‐thin AlO x coating (Figure S6b, Supporting Information), we determined a breakdown electric field of ≈5.7 MV cm –1 for a 5.5 nm thick alumina layer (Figure S6c, Supporting Information), which is consistent with literature [ 38 ] and demonstrates the applicability of the nc‐C/AlO x structure for field‐effect transistors.…”
Section: Resultssupporting
confidence: 87%
“…However, following this nucleation period, deposition of a nanometer‐thin conformal AlO x coating on the as‐deposited amorphous carbon layer was achieved. While charge carriers can directly tunnel through the nanometer‐thin AlO x coating (Figure S6b, Supporting Information), we determined a breakdown electric field of ≈5.7 MV cm –1 for a 5.5 nm thick alumina layer (Figure S6c, Supporting Information), which is consistent with literature [ 38 ] and demonstrates the applicability of the nc‐C/AlO x structure for field‐effect transistors.…”
Section: Resultssupporting
confidence: 87%
“…The DUV photochemical activation of sol–gel films revealed that an intense photon flux can deliver sufficient energy to the precursor film to decompose the organic species and form a dense M–O–M phase, similar to that achieved via high-temperature annealing (Figure a) . More recently, the DUV method was extended to various MO dielectrics including Al 2 O 3 and Zr-doped Al 2 O 3 (ZAO). ,, These dielectric films were fabricated by spin-coating aluminum nitrate nonahydrate/2-methoxyethanol and zirconium­(IV) acetyl-acetonate/2-methoxyethanol as Al and Zr sources, respectively, and the DUV process decomposed the precursors within 5 min at 253.7 nm via a radical-mediated mechanism . Both the film capacitance and leakage current increase as the Zr:Al molar ratio increases, with the optimal ZAO films (∼35 nm thick) having a Zr:Al molar ratio of 5:95.…”
Section: High-k Dielectric Materialsmentioning
confidence: 91%
“…118 Nevertheless, this configuration provides also direct light irradiation of the TiO 2 /M/environment interface, and charge carriers formed in its close proximity can thus be effectively transferred to reactants. 119 122 …”
Section: Tio 2 Nanotube Surfaces For Self-orderingmentioning
confidence: 99%